The Effect of Financial Literacy on The Financial Performance of Msmes Palopo City - Erna; Goso; Ibrahim Halim (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to determine the influence of financial literacy on the financial performance of MSMEs in Palopo City. The data used in this study is primary data of 99 MSMEs in the Pancasila Field, Palopo City. The sampling technique used is a technique based on convenience. The method used to analyze the relationship between independent variables and dependent variables is the simple linear regression method. The results of the analysis with SmartPLS show that financial literacy has a positive and significant effect on the performance of MSMEs in Palopo City. This shows that the importance of a business to have knowledge of finance is related to how recording techniques, bookkeeping, the level of business debt and the budget needed in running a business.